Estimation of over nutrition among the elderly population of India: a systematic review - Tripathi, Srishti; Banerjee, Debashmita; Murry, Benrithung (International Journal of Research in Medical Sciences, 2023)
India is undergoing a demographic transition where the unprecedented increase in percentage of elderly population is posing new public health challenges. Malnutrition increases health risks in the older population but the majority of research in elderly nutrition focuses on the aspect of under nutrition while over nutrition remains largely ignored. Over nutrition comprising over weight and obesity substantially reduces the likelihood of healthy ageing. Therefore, the aim of this systematic review is to estimate the status of over nutrition among elderly population of India. A systematic search was conducted in PubMed, Scopus and Google Scholar to identify relevant articles published during 2012 to 2022 following standard protocol and search terms. A total of 26 articles which were found to be relevant were analysed. Body mass index (BMI) based over nutrition is becoming a prevalent condition among the elderly of India. It was found more prevalent among elderly women compared to their male counterparts. Higher prevalence of over nutrition was found among urban dwelling elderly but its incidence is on rise among rural geriatric population. Overweight and obesity among older adults is a complex nutritional concern. So a holistic approach is needed to address this challenge.